Evaluación funcional de hombro en pacientes operados de fractura de clavícula - Aguilar García, Alex Miguel (2020)
Objective: To evaluate the functionality of the shoulder with the rapid DASH questionnaire to determine the function of the shoulder in patients operated on for clavicle fracture. Material and methods: Observational, descriptive and prospective study constituted by patients operated for fracture of clavicle Allman type 1 in the Regional Teaching Hospital of Trujillo during the period 01/11/16 to 10/31/17 and p <0.05 to find the significance Results: 91.67% presented a fast DASH <24 with a standard deviation of 16.97 ± 3.43; The male gender presented better functionality (98.67%), and of the female gender, 33% had poor functionality (p = 0.05); all young people and 92% of adults (31 to 50 years old) rapid presentation DASH <24 (p = 0.395); The least injured side was the right side, but it had the highest percentage (13.3%) that obtained fast DASH> 24 (p = 0.043). Conclusion: Allman type 1 clavicle fracture operated patients have good shoulder functionality.